Role of Renal Nerves in the Treatment of Renovascular Hypertensive Rats with L-Arginine - Sonia Alves Gouvea; Renata V. Tiradentes; Cintia H. Santuzzi; Vinícius Mengal; Henrique de A. Futuro Neto; Nyam F. Silva; Gláucia R. Abreu (International Journal of Hypertension)
The purpose was to determine the role of renal nerves in mediating the effects of antihypertensive treatment with L-arginine in a renovascular hypertension model. The 2K1C (two-kidney one-clip model) hypertensive rats were submitted to bilateral surgical-pharmacological renal denervation. The animals were subdivided into six experimental groups: normotensive control rats (SHAM), 2K1C rats, 2K1C rats treated with L-arginine (2K1C + L-arg), denervated normotensive (DN) rats, denervated 2K1C (2K1C + DN) rats, and denervated 2K1C + L-arg (2K1C + DN + L-arg) rats. Arterial blood pressure, water intake, urine volume, and sodium excretion were measured. The 2K1C rats exhibited an increase in the mean arterial pressure (MAP) (from 106 ± 3 to 183 ± 5.8 mmHg, P<0.01), whereas L-arg treatment induced a reduction in the MAP (143 ± 3.4 mmHg) without lowering it to the control level. Renal nerve denervation reduced the MAP to normotensive levels in 2K1C rats with or without chronic L-arg treatment. L-arg and denervation induced increases in water intake and urine volume, and L-arg caused a significant natriuretic effect. Our results suggest that renal sympathetic activity participates in the genesis and the maintenance of the hypertension and also demonstrate that treatment with L-arg alone is incapable of normalizing the MAP and that the effect of such treatment is not additive with the effect of kidney denervation.